Microwave processing of materials in metallurgy - Gasik , M.M. (Theory and Practice of Metallurgy, 2025)
The application of microwave technology in minerals processing and metallurgy is getting interest as it allows non-conventional treatment of depleted resources and has positive environmental and economic impact. Microwave processing provides rapid and selective heating with energy efficiency, in contrast to traditional methods. This work analysis some basic features of this technology and shows examples of modelling and experimental study of hybrid microwave treatment of oxide materials, highlighting differences in achievable temperatures and heating times. The model for experimental hybrid microwave furnace with cavity resonating in TM012 mode at 2.45 GHz with 2 kW power has been implemented in COMSOL software and tested on heating of zirconia samples with SiC based susceptor. Electric field and temperature distributions have been simulated and heating rate variations analysed in different positions of the cavity. Results of the analysis are discussed together with the potential use of microwave technology in ore treatment, mineral processing, smelting and carbothermic reduction. This technology has a very good potential in enhancing metal recovery, reducing energy consumption, and improving processing, but this requires understanding about how different materials reacts with microwaves and how the furnaces have to be optimized for a better sustainability.